Far from home: Morphological, ultrastructural, and molecular characterization of Thometrema patagonicum (Szidat, 1956) (Hemiuroidea: Derogenidae) from an unexpected host and locality, with taxonomic implications - Alves, Philippe Vieira; Ebert, Mariana Bertholdi; Silva, Ricardo Bassini (Cambridge University Press (CUP), 2025)
While most higher taxa in the Hemiuroidea exhibit remarkable diversity and thrive worldwide in marine ecosystems, a few groups have successfully radiated into freshwater environments. Among them, species of Thometrema are well known from freshwater and brackish fishes in the New World. In this study, specimens of Thometrema from a single specimen of the endangered pimelodid catfish Steindachneridion scriptum in the Upper Paraná River basin, State of São Paulo, Brazil, were subjected to morphological, ultrastructural (first scanning electron microscopy data for the genus) and molecular analyses. Newly obtained sequences of the partial large subunit nuclear ribosomal RNA (28S rDNA) and partial mitochondrial cytochrome c oxidase subunit I (COI mtDNA) provided strong evidence supporting the identification of the specimens as T. patagonicum, a trematode previously known only from endemic percichthyid fishes (Percichthyidae) in the Argentinian Patagonia. This unexpected finding, along with critical morphological evaluation of new and deposited material, led us to propose T. overstreeti and T. bonariense as junior synonyms of T. patagonicum. Moreover, we reassessed certain morphological features, revealed new potential distinguishing characters (papillae) and raised doubts about the taxonomic value of commonly used features for species differentiation (e.g., vitellarium masses). To overcome taxonomic problems in Thometrema due to the paucity of morphological features to clearly set species boundaries, new descriptions could leverage integrative approaches, as employed here, to establish robust species hypotheses and ultimately unravel the actual species composition in the Americas.